(untitled) (Acta Entomologica Serbica, 2019)
Seventeen very interesting species were found in studying the fauna of Geometridae of Serbia. Ten of them are new to the fauna of Serbia (Ennomos quercaria, Anticollix sparsata, Colostygia fitzi, Eupithecia absinthiata, E. alliaria, E. assimilate, E. millefoliata, E. semigraphata, Perizoma juracolaria and Trichopteryx polycommata); five are here recorded in Serbia for the second time (Dyscia raunaria, Elophos dilucidaria, Eupithecia ochridata, Perizoma bifaciata and Rhodostrophia discopunctata); and two are recorded for the third time (Nebula nebulata and Perizoma hydrata). Information regarding where and when they were all found is given herein.